Exploring Students' Adoption of Canvas Learning Management System in Programming at a State University in the Philippines: A Technology Acceptance Perspective - Dela Rosa, Aaron Paul Mallari (International Journal of Computing Sciences Research, 2023)
Purpose – Learning management systems (LMSs) became more prominent during the Coronavirus Disease 2019 (COVID-19) pandemic. Universities around the globe find the best solutions and which LMS is the best to deliver their education. This study determined the technology acceptance of using Canvas LMS Free for Teachers in delivering a programming course. Method – A descriptive survey method was implemented in this study on the students of Bulacan State University, a state university in the Philippines, who are taking Bachelor of Science in Information Technology (BSIT). Web Systems and Technologies 2 course was subjected to using Canvas LMS and was evaluated by the students. Results – Within the course, lessons in the form of modules were provided. Additionally, summative assessments were provided to the students at the end of each lesson. Third-year BSIT students were asked to evaluate the LMS used. Out of 169 students enrolled in the course, 132 students answered the survey questionnaire provided. Upon tabulating students’ responses, it was deemed found that they “Strongly Agree” with using Canvas LMS. In terms of its technicalities, the overall mean is M=4.52, which shows that Canvas LMS offers quality features fit for use in delivering programming courses. On the other hand, in terms of its presence, the overall mean is M=4.50, which shows that by using the LMS, students were able to learn the programming language being delivered asynchronously. Conclusion – The results show that Canvas LMS is one of the better options for delivering programming courses through asynchronous modalities. Recommendations – Other programming courses being offered in the university may utilize the same LMS. Additionally, with high results of acceptance, the university may consider a subscription to Canvas LMS to deliver its courses online. Research Implications – As the study’s findings highlighted the high acceptance of students on using Canvas LMS, this presents that utilizing a learning management system in programming is an effective approach as it offers features for programming courses.